Real time-PCR, ELISA, as an identification methods for Detection respiratory syncytial virus in children - Suad H. AL-Bashar; Amin Suliman Badawy; Belal Abdul-Rahman Mohammed (Tikrit Journal of Pure Science)
The study have been done to detecting HRSV infections among hospitalized children under 10 years old in Salahaldin Governorate, in addition to compare different diagnostic methods for detection of this virus.